Antifungal Activity of Methanol Extract of Mikania micrantha Kunth. Leaves Against Malassezia furfur - Rahmawati Rahmawati; Evi Nurmeiti; Diah Wulandari Rousdy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
West Kalimantan experiences a tropical climate characterized by elevated humidity, which creates an environment conducive to the proliferation of Pityriasis versicolor due to Malassezia furfur. Plants with medicinal properties that include alkaloids, flavonoids, phenols, terpenoids, tannins, and quinones, such as sembung rambat (Mikania micrantha Kunth.), represent promising sources of antifungal compounds. This research sought to assess the antifungal efficacy of the methanol extract from sembung rambat leaves against Malassezia furfur in a laboratory setting and to identify its minimum inhibitory concentration. The disc diffusion technique was employed with extract concentrations of 20%, 25%, 30%, and 35%. Ketoconazole at 2% acted as the positive control, while sterile distilled water was utilized as the negative control. The diameters of the inhibition zones were evaluated using the Kruskal-Wallis test, accompanied by Duncan's multiple range test. The findings indicated that all concentrations of the extract successfully suppressed the growth of Malassezia furfur. The minimum inhibitory concentration was established at 20%, resulting in an inhibition zone measuring 0.48 cm in diameter after 48 hours of incubation. The methanol extract of sembung rambat leaves displayed a fungistatic action against Malassezia furfur in vitro.